The essentials of computer organization and architecture - Null, Linda; Lobur, Julia (Jones & Bartlett Learning, 2015)
In its fourth edition, this book focuses on real-world examples and practical applications and encourages students to develop a "big-picture" understanding of how essential organization and architecture concepts are applied in the computing world. In addition to direct correlation with the ACM/IEEE CS2013 guidelines for computer organization and architecture, the text exposes readers to the inner workings of a modern digital computer through an integrated presentation of fundamental concepts and principles. It includes the most up-to-the-minute data and resources available and reflects current technologies, including tablets and cloud computing. All-new exercises, expanded discussions, and feature boxes in every chapter implement even more real-world applications and current data, and many chapters include all-new examples. -- Edited summary from book